The Influence of Discounts and Cashback on Purchasing Decisions Through Perceived Value and Trust in Shopee Consumers - Omega Cristiani; Finnah Fourqoniah (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of discounts and cashback on purchasing decisions by considering the mediating role of perceived value and trust among Shopee consumers in Samarinda City. The study used a quantitative approach with an associative method, involving 400 respondents selected through purposive sampling. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results showed that discounts significantly influenced purchasing decisions, while cashback did not have a significant direct effect. Discounts and cashback were shown to significantly influence perceived value and trust. Furthermore, perceived value and trust also significantly influenced purchasing decisions. In the mediation analysis, discounts significantly influenced purchasing decisions through perceived value and trust. Meanwhile, cashback did not significantly influence perceived value, but did have a significant effect through trust. This study demonstrates that the effectiveness of promotional strategies is determined not only by price incentives but also by their ability to shape consumer perceptions of value and trust.